Emerging Microwave Technologies in Industrial, Agricultural, Medical and Food Processing - Yeow You, Kok (IntechOpen, 2018)
Recently, the rapid development of microwave technologies has had a significant impact on current industrial, agricultural, medical, and food processing fields. This book is a self-contained collection of valuable scholarly papers related to the microwave applications. This book contains 10 chapters that cover several subtopics of the microwave engineering, namely, microwave system design models, emerging microwave devices, and microwave heating/drying technologies. Hence, this book should be useful to the academics, scientists, practicing researchers, and postgraduate students whose works are related to microwave technologies.